2010
DOI: 10.1080/10942910902968726
|View full text |Cite
|
Sign up to set email alerts
|

Volatile Components in Three Commercial Douchies, A Chinese Traditional Salt-Fermented Soybean Food

Abstract: Douchi is a traditional fermented soybean product originated in China and it has been consumed since ancient times as seasoning for food. Volatile components of three commercial douchies were extracted using a simultaneous steam distillation and extraction apparatus (SDE). The extracts were analyzed by gas chromatography-mass spectrometry (GC-MS). A total of 131 compounds were identified, but only 25 components were common to all three brands. Major classes of compounds included esters (29), acids (18), alcoho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Zhang et al [10] reported that glutamic acid was high in both the natural and artificial types of Yongchuan douchi, which contributes to its umami taste, and the amount of bitter amino acids including isoleucine, leucine and arginine were higher in artificial Yongchuan douchi. Wang et al [11] isolated and identified 131 kinds of volatile compounds from three kinds of commercial tempeh by simultaneous distillation and extraction with gas chromatography−mass spectrometry (SDE-GC-MS), mainly esters, acids and alcohols. In addition, only a small part of the volatile compounds detected by the GC-MS contributed to food flavor, namely the aroma-active compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al [10] reported that glutamic acid was high in both the natural and artificial types of Yongchuan douchi, which contributes to its umami taste, and the amount of bitter amino acids including isoleucine, leucine and arginine were higher in artificial Yongchuan douchi. Wang et al [11] isolated and identified 131 kinds of volatile compounds from three kinds of commercial tempeh by simultaneous distillation and extraction with gas chromatography−mass spectrometry (SDE-GC-MS), mainly esters, acids and alcohols. In addition, only a small part of the volatile compounds detected by the GC-MS contributed to food flavor, namely the aroma-active compounds.…”
Section: Introductionmentioning
confidence: 99%
“…These hydroxy acids are also present in other biological matrixes such as honey [ 27 , 28 ]. Furthermore, 2OH4MP has been found in roasted cocoa [ 29 ], fermented soybean [ 30 ] and cyanobacteria [ 31 ]. 3OHBc is present in grape leaf tissue [ 32 ] and has been proposed as a biomarker of grape fungal resistance by Batovska et al [ 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…versatilis may lead to an increase of aldehydes. Benzaldehyde, benzene acetaldehyde and 5‐methyl‐2‐phenyl‐2‐hexenal were the major volatile components detected in commercial Douchi and other traditional fermented condiments in far eastern (Wang et al ., ). Most aldehydes detected in the Douchi endowed characteristic aromas.…”
Section: Resultsmentioning
confidence: 97%